H-index pathology: implications for medical researchers and practitioners. (15th December 2009) - Horne, Rob; Petrie, Keith J; Wessely, Simon
Abstract : The h-index has quickly become the standard method by which medical schools judge the impact of medical researchers. Rob Horne, Keith Petrie, and Simon Wessely describe a cluster of potentially pathological behaviours associated with the index.